1988
DOI: 10.1002/bem.2250090403
|View full text |Cite
|
Sign up to set email alerts
|

Slow potentials and spike unit activity of the cerebral cortex of rabbits exposed to microwaves

Abstract: Unanesthetized rabbits exposed to 12.5-cm microwaves at a field intensity of 40 mW/cm2 in the region of the head showed an increase in the number of slow waves and spindle-shaped firings in the EEG and a change in the discharge frequency of neurons in the visual cortex in 41-52% of the cases. An enhancement of the evoked response of visual cortex neurons to light was observed in 61% of the cases and a facilitation of the driving response in 80% of all cases. It is concluded that the evoked response is a more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Despite extensive research in the field of low-level microwave effects on the nervous system during recent decades (Johnson and Guy, 1972;Bawin et al, 1973;Baranski and Edelwejn, 1975;Gavalas-Medici and Day-Magdaleno, 1976;Chizhenkova, 1988;Mann and Roschke, 1996;Vorobyov et al, 1997;Wagner et al, 1998;Lutty et al, 2000), the reports of possible effects are often contradictory and the mechanisms behind the effects are still unclear. The difficulties in independent repeating of the experimental results cause doubt in these effects.…”
Section: Thermal and Non-thermal Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Despite extensive research in the field of low-level microwave effects on the nervous system during recent decades (Johnson and Guy, 1972;Bawin et al, 1973;Baranski and Edelwejn, 1975;Gavalas-Medici and Day-Magdaleno, 1976;Chizhenkova, 1988;Mann and Roschke, 1996;Vorobyov et al, 1997;Wagner et al, 1998;Lutty et al, 2000), the reports of possible effects are often contradictory and the mechanisms behind the effects are still unclear. The difficulties in independent repeating of the experimental results cause doubt in these effects.…”
Section: Thermal and Non-thermal Effectsmentioning
confidence: 96%
“…Several investigators have reported that microwave exposure produces different alterations in the EEG signal: an increase in the number of slow rhythms in the EEG of rabbits (Chizhenkova, 1988), modulated at brain rhythm frequencies EMF affect EEG patterns in the cat (Bawin et al, 1973), a significant elevation of the EEG hemispheric asymmetry during the first 20 seconds of the stimulation period (Vorobyov et al, 1997).…”
Section: Thermal and Non-thermal Effectsmentioning
confidence: 99%
“…The changes analyzed in this study for brain signals in different sleep-wake states are found in agreement with previous published reports. 10,12,23,33,50 However, from literature review, it is evident that the changes in EEG frequencies are highly dependent on the exposure frequency, time of exposure, and the modulation frequency. Thus, in these conditions, the findings of the present study for EEG power spectrum analysis are unique.…”
Section: Discussionmentioning
confidence: 96%
“…Microwaves, acting selectively on the nervous tissue, induce substantial electrophysiological and neuromorphological changes in the peripheral, intermediate, and central parts of the visual analyzer [4,7,9,11]. However, the nature of alterations in the synaptic apparatus at different levels of the visual system and their contribution in microwave-induced visual disorders have been little studied.…”
Section: Abstract: Visual Analyzer Synapses Microwavesmentioning
confidence: 99%